2016
DOI: 10.1242/bio.016899
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, anti-biofouling and drag-reduction properties of a biomimetic shark skin surface

Abstract: Shark skin surfaces show non-smoothness characteristics due to the presence of a riblet structure. In this study, biomimetic shark skin was prepared by using the polydimethylsiloxane (PDMS)-embedded elastomeric stamping (PEES) method. Scanning electron microscopy (SEM) was used to examine the surface microstructure and fine structure of shark skin and biomimetic shark skin. To analyse the hydrophobic mechanism of the shark skin surface microstructure, the effect of biomimetic shark skin surface microstructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 26 publications
1
72
0
Order By: Relevance
“…The effect of the movement of the appendage on four-legged animals in a slope also requires comprehensive understanding. In this study, the trajectory of the head centroid movement of a goat on a slope is measured and its influence on the stability is analyzed to solve the problem of irregular ground walking of current small machinery [21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the movement of the appendage on four-legged animals in a slope also requires comprehensive understanding. In this study, the trajectory of the head centroid movement of a goat on a slope is measured and its influence on the stability is analyzed to solve the problem of irregular ground walking of current small machinery [21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these methods are always time‐consuming, expensive, and size‐limited. Some other methods, including surface wrinkling, self‐masking reactive‐ion etching, nano‐imprinting lithography, and relevant biomimetic fabrication methods cannot control the period and height of the surface micro‐grooves precisely. Because of the lack of suitable fabrication methods, systematic studies about the influences of anisotropic groove‐like microstructures on the anisotropic sliding behavior are insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…The grain boundary etched SS316L displayed hydrophobicity and microscale structure, which can prevent bio-fouling, thereby further reducing the probability of localized corrosion initiation in a maritime environment. [21][22][23]26,31,32 Preliminary investigations have indeed shown that the surface topography on SS316L achieved by potentiostatic polarization can significantly reduce the adhesion of bacteria compared to the surfaces of as-received and electro-polished SS316L. An in-depth study of the correlation between SS316L surface topography and biofouling is currently underway, but discussion of these results is outside the scope of the current paper.…”
Section: Resultsmentioning
confidence: 92%